THE WORK CULTURE INTEGRATION OF HINDU RELIGIOUS EXTENSION AGENTS WITH PARISADA IN COMMUNITY DEVELOPMENT IN TABANAN - I Wayan Sukabawa; A.A. Made Putra Arsana (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
This study aimed to uncover, understand, describe, and analyze facts about the work cultureintegration of the Hindu Religious Extension Agent with Parisada in Community Development inTabanan. The work culture established by the Hindu institution between the Hindu ReligiousExtension Agents and Parisada intended to improve work ethics as a service to the people. This isimportant to do to improve a positive image as a religious institution for religious communitiesunder the Ministry of Religious Affairs in the community. The work culture has been agreed upon,which are the right and appropriate values to improve the state apparatus performance, namelyHindu Religious Extension Agents to provide excellent service to the community.